Comparative advantage of Ethiopian textile and apparel industry. (9th September 2019) - Rundassa, Merertu Wakuma; Azene, Daniel Kitaw; Berhan, Eshetie
Abstract : Purpose: Ethiopia's economy is primarily based on agriculture, but starting form 2010, the government has been determined to diversify the exports with a priority set for strategic sectors like light manufacturing in which textile and apparel manufacturing industries are included. The purpose of this paper is to measure the comparative advantages of the Ethiopian textile and apparel industry using the revealed comparative advantage (RCA) in the period from 2007 to 2016. Design/methodology/approach: For the purpose of the paper, secondary data were collected from the UN comtrade site, and related data sources were cited in the literature review for the purpose of triangulation (cross-checking of the analysis with theoretical background). From the theoretical background, the two indices of RCA (Balassa index and Lafay index) were used for the evaluation of the industries' competitive advantage and to identify which industry (textiles or apparel) was of more importance in the country. Findings: The findings of the study showed that Ethiopia was more competitive in the textile sector. However, and with reference to the Lafay index, the country has been focusing on apparel sector, because of the opportunities for job creation. Research limitations/implications: For the purpose of this study, secondary data were used and the general conclusions are limited to the corresponding sources of data. Practical implications: Because of the labor-intensive nature, the textile and apparel sector has been one of the areas promoted by the Ethiopian Government in its industrialization policy. The finding of this paper can be used by policy makers to evaluate the competitiveness of the country. Social implications: The findings can be used to assess social upgrading issues in the textile and apparel sector. Originality/value: The work is the first of its kind in the sector as well as the country.